Are Eight Hands Better Than Seven? A Palaeographic Study of the Scribal Hand Division of AM 624 4to - Macháčková, Nikola, 1993- (2019)
AM 624 4to, a 15th-century manuscript containing texts that mostly concern religious or scientific matters, was obtained by Árni Magnússon in 1702. Its journey from its place of origin in the north-west of Iceland, to Copenhagen and then to Reykjavík is an exciting tale. The manuscript as a whole, however, has not received much scholarly attention, and the only recognised scribal hand belongs to Jón Þorvaldsson, who was an abbot of Þingeyraklaustur until 1514 and an active scribe. The scholars who have examined the manuscript present different conclusions about the distribution of scribal hands; and there are several sections in the manuscript where it is particularly difficult to resolve the hand distribution. The principal aim of this thesis, therefore, is to determine how many scribal hands were involved in the writing of this manuscript, and at exactly which points of the manuscript they change. In order to establish the scribal hand division of the manuscript, this thesis analyses individual letterforms – with an emphasis of the letters with ascenders and descenders – and selected abbreviation marks. Based on a combination of the palaeographic features of these letterforms and abbreviation marks, I make the conclusion that AM 624 4to was written by eight different scribal hands. This conclusion includes a new theory about the scribal hand division of the problematic section. This thesis is not only the first coherent study of AM 624 4to and its scribal hand division but could also serve as an exemplar for future palaeographic studies of a similar kind. AM 624 4to er handrit frá 15. öld sem inniheldur texta af trúarlegum eða vísindalegum toga og komst í hendur Árna Magnússonar árið 1702. För handritsins frá ritunarstað sínum á norðvesturhluta Íslands til Kaupmannahafnar og síðar til Reykjavíkur er afar áhugaverð. Handritið í heild sinni hefur ekki fengið mikla athygli frá fræðimönnum og er eini þekkti skrifari handritsins Jón Þorvaldsson, ábóti Þingeyrarklausturs til ársins 1514 og virkur skrifari. ...